Testing and Validation of Computer Simulation Models : Principles, Methods and Applications - Murray-Smith, David J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This must-read text/reference provides a practical guide to processes involved in the development and application of dynamic simulation models, covering a wide range of issues relating to testing, verification and validation. Illustrative example problems in continuous system simulation are presented throughout the book, supported by extended case studies from a number of interdisciplinary applications. Topics and features: Provides an emphasis on practical issues of model quality and validation, along with questions concerning the management of simulation models, the use of model libraries, and generic models Contains numerous step-by-step examples Presents detailed case studies, often with accompanying datasets for readers to use in model validation and testing exercises Includes discussion of hybrid models, which involve a combination of continuous system and discrete-event descriptions Examines experimental modeling approaches that involve system identification and parameter estimation, emphasizing the practical importance of more theoretical concepts such as identifiability and test input design Offers supplementary material at an associated website, including links for readers without prior experience in this field to expand their background knowledge This highly useful, hands-on work will be of great benefit to practitioners and professionals who use simulation and modeling techniques in their work, as well as to students in graduate-level courses on modeling and simulation. Dr. David Murray-Smith is an Emeritus Professor and Honorary Senior Research Fellow at the University of Glasgow.
An Introduction to Simulation Models and the Modelling Process -- Concepts of Simulation Model Testing, Verification and Validation -- Measures of Quality for Model Validation -- Sensitivity Analysis for Model Evaluation -- Experimental Data for Model Validation -- Methods of Model Verification -- Methods for the Invalidation/Validation of Simulation Models -- Management Issues within Simulation Model Development and Testing -- Case Study: Development and Testing of a Simulation Model of Two Interconnected Vessels -- Case Study: Model Validation and Experiment Design for Helicopter Simulation Model Development and Applications -- Case Study: Compartmental Models of the Gas-Exchange Processes of the Human Lungs -- Case Study: Modelling of Elements of the Neuromuscular -- Systems Involved in the Regulation of Posture and Control of Movement -- Further Discussion.
Keywords: Computer simulation; Engineering mathematics; Microprogramming; Human physiology; Simulation and Modeling; Mathematical Applications in Computer Science; Mathematical and Computational Engineering; Control Structures and Microprogramming; Human Physiology